Bank branches efficiency under management and regulatory constraints - Ferro, Gustavo Adolfo (2019)
The main purpose of this paper is to assess the cost-efficiency of Banco Ciudad de Buenos Aires’s bank branches using a Stochastic Frontier Analysis (SFA). Owing to the results, management can decide on a new branching dimension. Also, if some regulatory or managerial limits could be lifted, such as the closure or opening of new branches without central bank authorization, or redundancy staff reduction, the results could be important for management. We identify best and worst behaved branches. The more cost-efficient branches and the least costefficient ones differ in their size and input mix. Nonetheless, they present a similar output mix.